Pengaruh Kualitas Pelayanan, Harga dan Lokasi terhadap Keputusan Konsumen Berbelanja di Alfamart Ende - Costa, Darminya Rahayu Da; Leha, Ernesta; Penu, Yustina Paulina (Program Studi Ekonomi Pembangunan Universitas Flores, 2023)
This study aims to determine the effect of service quality, price and location on shopping decisions. This study uses the causal associative method and uses aquantitative approach with a sample of 100 people. The data collection technique uses a questionnaire. The analysis technique used is Multiple Linear Regression.The results of this study indicate that the first variable quality of service affects shopping decisions for Alfamart customers, this is evidenced by the results of thesignificance test (t count = 1.987, significance value 0.000 < 0.05 and regression coefficient = 0.112) Both price variables affect shopping decisions for customers.at Alfamart, this is evidenced by the results of the significance test (t count = 3.485, significance value 0.001 < 0.05 and regression coefficient = 0.281) The threelocation variables affect the shopping decision of customers at Alfamart, this is evidenced by the results of the significance test (t count = 2.434, significance value0.001 < 0.05 and regression coefficient = 0.234) and service quality, price and location simultaneously influence shopping decisions for Alfamart customers withsignificance test results (F count = 55,889 with a significance value of 0.000 < 0.05)